SAVER.NET LIDAR NETWORK IN SOUTHERN SOUTH AMERICA - Ristori, Pablo; Otero, Lidia; Jin, Yoshitaka; Barja Gonzalez, Boris; Shimizu, Atsushi; Barbero, Albane; Salvador, Jacobo; Bali, Juan Lucas; Herrera, Milagros; Etala, Paula; Acquesta, Alejandro; Quel, Eduardo; et al. (My University, 2018)
The South American Environmental Risk Management Network (SAVER-Net) is an instrumentation network, mainly composed by lidars, to provide real-time information for atmospheric hazards and risk management purposes in South America. This lidar network have been developed since 2012 and all its sampling points are expected to be fully implemented by 2017. This paper describes the network's status and configuration, the data acquisition and processing scheme (protocols and data levels), as well as some aspects of the scientific networking in Latin American Lidar Network (LALINET). Similarly, the paper lays out future plans on the operation and integration to major international collaborative efforts.
Keywords: Network monitoring; Instrumentation